The Implementation of Preliminary State Defense Education in Shaping the Character and State Defense Awareness of Students at Pakuan University Based on Pancasila Values - Meisya Nayara Hermanita; Yogi Winarto; Bilqis Azzahra Wanti; Lugas Anugrah; Herli Antoni (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the implementation and effectiveness of the Preliminary State Defense Education (PPBN) program at Pakuan University in shaping student character and enhancing national defense awareness based on Pancasila values. As globalization intensifies and individualistic ideologies increasingly influence youth, instilling civic responsibility and national identity has become more challenging. Employing a qualitative-descriptive approach, this research evaluates program outcomes through document analysis, stakeholder reports, and thematic insights into student engagement. The findings indicate that PPBN—though conducted over only three days—has succeeded in introducing core values such as nationalism, solidarity, and social responsibility. However, the short duration and varying levels of student motivation limit long-term value internalization. To improve effectiveness, the study recommends integrating civic values into broader curricular and extracurricular programs, incorporating digital and immersive learning tools, and expanding partnerships with external institutions. Alumni involvement and gamification are also proposed as innovative strategies to maintain student interest and deepen experiential learning. Overall, PPBN is a strategic initiative in national character education, yet it requires continuous innovation and policy support to remain relevant and impactful. This study contributes to the discourse on civic education in higher education and offers insights for curriculum developers and policymakers seeking to strengthen national identity in a globalized era.